2006
DOI: 10.1097/01.brs.0000194840.42792.f2
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Analysis of Intervertebral Separation With a 0° and 30° Rope Angle Using the Saunders Cervical Traction Device

Abstract: The research findings may have treatment implications when applying cervical traction with the SCTD. Further research using subjects with cervical nerve root compression will need to be conducted to substantiate clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
2
12
0
1
Order By: Relevance
“…Considering the reliability tests within and between examiners in the present study, the ICCs for measuring the intervertebral disc spaces were consistent with those in the previous studies [7,34]. Our percentage of relative errors in measuring the disc heights among segments (2.1%-3.2%) was similar to the measurement error in the study by Frobin et al [7].…”
Section: Evaluation Of Errors and Repeatabilitysupporting
confidence: 80%
See 2 more Smart Citations
“…Considering the reliability tests within and between examiners in the present study, the ICCs for measuring the intervertebral disc spaces were consistent with those in the previous studies [7,34]. Our percentage of relative errors in measuring the disc heights among segments (2.1%-3.2%) was similar to the measurement error in the study by Frobin et al [7].…”
Section: Evaluation Of Errors and Repeatabilitysupporting
confidence: 80%
“…Previous researches suggested that traction forces of 11-16 kg were necessary to elicit a measurable change in cervical spine structures [3,32,36,37]. The sustained traction was usually applied to the disc herniation patients with a time period from 2 to 20 min depending on their conditions, and the 3-5 min was often suggested for the first treatment [22,32,34]. Therefore, the cervical traction force was adjusted to 25% of individual body weight for a 5 min continuous traction in our experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the X-ray findings were compared before and after traction, they revealed the increase of intervertebral disc space. There was also observed the improvement of functional ability of the examined patients on the basis of the NDI Questionnaire (Neck Disability Index Questionnaire) [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Many patients reported malaise during a few minutes' session. These were usually patients with obesity or those with gastrointestinal symptoms [1,8,25]. It seems that the need to fasten the patient with stabilization belts can further contribute to the development of these particular problems.…”
Section: Discussionmentioning
confidence: 99%